THE INFLUENCE OF KNOWLEDGE MANAGEMENT AND WORK-LIFE BALANCE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH JOB SATISFACTION: PENGARUH KNOWLEDGE MANAGEMENT DAN WORK-LIFE BALANCE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI JOB SATISFACTION - Medya Sari Rachma Atika; Anang Kistyanto; Andre Dwijanto Witjaksono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research was conducted with the aim of analiyzing the influence of Knowledge Management (KM) and Work-Life Balance (WLB) on Organizational Citizenship Behavior (OCB) through Job Satisfaction (JS) at Surabaya City of Government, Regional Secretariat. The research was carried out by distributing questionnaires related to the KM, WLB, JS and OCB variables to respondents. The number of respondents taken was 192 people from 368 total of employees. Structural Equation Model Partial Least Square (SEM PLS) is used as methodology and the data processed using Smart PLS 3. The research results show that KM and JS have a positive effect on OCB, but WLB does not have a significant effect on OCB. Furthermore for indirect relationships, JS acts as a mediator for the relationship between KM and OCB and WLB and OCB. Hopefully, this research can be taken into consideration by Surabaya City of Government, Regional Secretariat in improving the implementation both of KM and WLB, in order to improving OCB.